Syn‐depositional thin‐ and thick‐skinned extensional tectonics in the mid‐Cretaceous Lasarte sub‐basin, western Pyrenees. (19th April 2013) - Bodego, Arantxa; Agirrezabala, Luis M.
Abstract In the mid‐Cretaceous Lasarte sub‐basin (LSB) [northeastern Basque‐Cantabrian Basin (BCB)] contemporaneous and syn‐depositional thin‐ and thick‐skinned extensional tectonics occur due to the presence of a ductile detachment layer that decoupled the extension. Despite the interest in extension modes of rift basins bearing intra‐stratal detachment layers, complex cases remain poorly understood. In the LSB, field results based on mapping, stratigraphic, sedimentological and structural data show the relationship between growth strata and tectonic structures. Syn‐depositional extensional listric faults and associated folds and faults have been identified in the supra‐detachment thin‐skinned system. But stratigraphic data also indicate the activation of sub‐detachment thick‐skinned extensional faults coeval with the development of the thin‐skinned system. The tectono‐sedimentary evolution of the LSB, since the Late Aptian until the earliest Late Albian, has been interpreted based on thin‐ and thick‐skinned extensional growth structures, which are fossilized by post‐extensional strata. The development of the thin‐skinned system is attributed to the presence of a ductile detachment layer (Upper Triassic Keuper facies) which decoupled the extension from deeper sub‐detachment basement‐involved faulting under a regional extensional/transtensional regime.